The Sustainability of Fish Consumption in Romania: Customer Behaviour prior and after the Country's Adherence to the EU - Vlad Rosca; Raluca Ignat (Amfiteatru Economic Journal, 2014)
Using two sets of bivariate analyses in SPSS, we have tried to find out how sustainable the fish consumption in Romania is. We have used numerical variables, computed based on primary data obtained from Eurostat and the National Institute of Statistics. Two different timespans have been considered: the one prior to the country's adherence to the European Union and the one after. Using the two timespans let us compare the pre- and post-adherence situations, in order to see if the subsidies offered by the EU have had any effect on the sustainability of the environment.
Keywords: E21; F15; F40; Q25; Q52; Q53; Q57; 330; sustainable consumption; customers; sustainability; aquaculture; captures from inland waters; index of real earnings